Odpowiedź :
Cześć!
Korzystając ze wzoru skróconego mnożenia na kwadrat różnicy:
[tex](a-b)^2=a^2-2ab+b^2[/tex]
[tex](2\sqrt3-3\sqrt6)^2 =[/tex]
Niech [tex]a=2\sqrt3[/tex], [tex]b=3\sqrt6[/tex], wówczas:
[tex](2\sqrt3-3\sqrt6)^2 =(2\sqrt3)^2-2\cdot 2\sqrt3 \cdot 3\sqrt6 + (3\sqrt6)^2 = 4\cdot 3 - 12\sqrt18 +9\cdot 6=\\\\= 66 -36\sqrt2[/tex]
Pozdrawiam!
Odpowiedź:
= ( 2√3)² - 2* 2√3*3√6 + ( 3√6)² = 4*3 - 12*[tex]\sqrt{3*6}[/tex] + 9*6=
= 12 - 12 [tex]\sqrt{9*2}[/tex] + 54 = 66 - 12 [tex]\sqrt{9} *\sqrt{2} =[/tex] 66 -12*3 [tex]\sqrt{2}[/tex] = 66 - 36 √2
Szczegółowe wyjaśnienie:
(a - b)² = a² -2 a*b + b²
[tex]\sqrt{a*b} = \sqrt{a} * \sqrt{b}[/tex]